Coumarin Boosts Optimal Bone Remodeling Through Blocking AGE-RAGE Interaction in Diabetic Osteoblasts and Osteoclasts - Eun-Jung, Lee (Curr Dev Nutr, 2020)
OBJECTIVES: Accumulating evidence has shown that the risk of osteoporotic fractures is increased in patients with diabetes mellitus despite normal or high bone mineral density. Thus, diabetes-induced bone fragility has been recently recognized as a diabetic complication. Because the fracture risk is independent of the reduction in bone mineral density, deterioration of the bone quality may be the main cause of bone fragility. Coumarin is naturally found in many plants as phenylpropanoids and present in tonka beans at notably high concentrations. The purpose of this study was to identify that hyperglycemia-mediated advanced glycation end-product (AGE) resulted in impaired bone remodeling and to examine whether coumarin was capable of preventing diabetic osteoporosis through boosting bone remodeling. METHODS: The in vitro study employed osteoblastic MC3T3-E1 cells that were exposed to 33 mM glucose for 6 days in the presence of 1–20 μM coumarin. Alkaline phosphatase (ALP) activity was quantitatively determined in osteoblastic cells by using stable p-nitrophenyl phosphate. In addition, murine macrophage Raw 264.7 cells were differentiated to multi-nucleated osteoclasts with receptor activator of nuclear factor-κΒ ligand (RANKL) in 33 mM glucose and 1–20 μM coumarin for 5 days. RESULTS: High glucose attenuated the ALP activity of osteoblastic cells, which was enhanced by treating 1–20 μM coumarin to cells. On the other hand, 33 mM glucose diminished TRAP and bone resorption activity in RANKL-differentiated osteoclasts, indicating that osteoclast activation was impaired under diabetic conditions. On the contrary, coumarin elevated osteoclastic differentiation and activation. In addition, coumarin ameliorated aberrant bone remodeling in osteoblasts and osteoclasts evoked by AGE. Together, coumarin improved bone remodeling impaired in diabetic osteoblasts and osteoclasts though suppressing interaction of AGE and its receptor. CONCLUSIONS: These findings suggest the possibility that coumarin might be a potential agent for the treatment of diabetic osteoporosis. FUNDING SOURCES: This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MSIT) (2019R1A2C1003218).